Biosynthesis Of Poly(3-Hydroxybutyrate-Co-3- Hydroxy-4-Methylvalerate) Copolymer By Chromobacterium sp. USM2 - Ling, Siew Chen (2012)
Polyhydroxyalkanoate (PHA) with enhanced physicochemical properties will be ideal for a wide range of practical applications. The incorporation of 3-hydroxy- 4-methylvalerate (3H4MV), a branched C6-monomeric unit into the polymer backbone is known to improve the overall properties of the resulting polymer. However, the most suitable microorganism and PHA synthase that can synthesize and polymerize this monomer efficiently still remain unknown at present. In this study, the ability of Chromobacterium sp. USM2 to synthesize poly(3- hydroxybutyrate-co-3-hydroxy-4-methylvalerate) [P(3HB-co-3H4MV)] was evaluated under different culture conditions. It was found that Chromobacterium sp. USM2 can synthesize P(3HB-co-3H4MV) when glucose and isocaproic acid were fed as carbon sources. However, the highest molar fraction of 3H4MV, 22 mol% was detected in Chromobacterium sp. USM2 when isocaproic acid was provided as the sole carbon source. In addition, dissolved oxygen concentration was identified as a crucial factor in initiating the accumulation of high 3H4MV molar fractions. The structural configuration of the resulting P(3HB-co-3H4MV) was confirmed by FTIR, 1D and 2D NMR spectroscopy analysis. Subsequently, the thermal and tensile properties of P(3HB-co-3H4MV) copolymer was characterized. P(3HB-co-3H4MV) copolymer with Mw in the range of 5.4 x 105–9.3 x 105 Da were produced. TGA analysis and tensile test further revealed that the incorporation of small amounts of 3H4MV into 3HB polymer chain resulted in greater flexibility and thermal stability compared to P(3HB) homopolymer.